1985
DOI: 10.1177/001698628502900408
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Students in a Program of Radical Acceleration at the University Level

Abstract: The academic performance of 24 academically accelerated students (mean age at matriculation = 14 years) was compared with that of two groups of college students averaging four years older: 24 matched to the accelerants on pre-entry academic aptitude test scores (or "readiness"), and 24 National Merit Scholars. Accelerated students earned cumulative grade point averages comparable to those earned by National Merit Scholars and significantly higher than those earned by university students matched on pre-entry ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…The rapidity of changes in self-concept are critical given the relatively short duration of the experiment. While research among gifted students reveals relatively high levels of self-concept before any treatment (Janos & Robinson, 1985) and that short-term alterations in self-concept among the gifted are common (Olszewski-Kubilius, Ku- , 1989), similar examinations among students with learning disabilities have revealed relatively low pretreatment self-concept due to a general tendency to place blame for failure on themselves while attributing success to externalized factors (Bryan & Bryan, 1986, p. 203). The analysis of creative productivity found that 27 of the 108 gifted/LD students involved in this study initiated 27 Type III projects, and 21 were deemed by students and teachers to have been completed.…”
Section: Resultsmentioning
confidence: 99%
“…The rapidity of changes in self-concept are critical given the relatively short duration of the experiment. While research among gifted students reveals relatively high levels of self-concept before any treatment (Janos & Robinson, 1985) and that short-term alterations in self-concept among the gifted are common (Olszewski-Kubilius, Ku- , 1989), similar examinations among students with learning disabilities have revealed relatively low pretreatment self-concept due to a general tendency to place blame for failure on themselves while attributing success to externalized factors (Bryan & Bryan, 1986, p. 203). The analysis of creative productivity found that 27 of the 108 gifted/LD students involved in this study initiated 27 Type III projects, and 21 were deemed by students and teachers to have been completed.…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been made available by only a minority of American colleges and universities (Fluitt & Strickland, 1984;Karnes & Chauvin, 1982), carefully chosen and well supported early entrants are more likely to complete baccalaureate degrees than other academically talented youths, and they earn higher grades and more academic honors while so doing (Daurio, 1979;Eisenberg & George, 1979;Janos, 1987;Janos & Robinson, 1985a;Keating, 1976;Pressey, 1967;Stanley, 1985;Stanley & Benbow, 1983a, 1983cStanley, Keating, & Fox, 1974;Terman & Oden, 1947). Moreover, early completion of advanced graduate training has been found to be associated with increased scientific and scholarly productivity Stanley & Benbow, 1983b).…”
Section: Introductionmentioning
confidence: 99%
“…Carefully selected, intellectually capable adolescents who enter college at an early age are often highly successful in their academic work (Fund for the Advancement of Education, 1953Education, , 1957Janos & Robinson, 1985;Pressey, 1967;Stanley, 1985;Stanley & McGill, 1986). Nevertheless, there is widespread concern that accelerants are vulnerable to personality adjustment problems (Daurio, 1979;Montour, 1976Montour, , 1977Southern, Jones, & Fiscus, 1989).…”
mentioning
confidence: 99%